Azobenzene: A Photoactive Building Block for Supramolecular Architectures. Issue 7 (5th January 2017) - Baroncini, Massimo; Bergamini, Giacomo
Abstract: The development of nanoscale systems capable to perform specific functions under external control is a challenging task and a fascinating objective in Chemistry. Photochromic compounds undergo radical changes in their physico‐chemical properties upon light excitation, for this reason they are valuable building blocks for the construction of photo‐controllable molecular devices, machines and materials. The E–Z photoisomerization of azobenzene has been known for almost 80 years and – owing to its high efficiency and excellent reversibility – has been widely employed to introduce an element of photo‐control in a large variety of compounds, biomolecules, nanosystems and materials. Here we present some of our research results highlighting how this outstanding photochrome can be utilized to develop systems with light‐induced functionalities. Abstract : In this Account we report some examples in which azobenzene moieties are contained into supramolecular structures and how the photoisomerization achieves precise and clean control on some of their properties. These results highlight how this outstanding photochrome can be used to develop molecular devices and machines with light‐induced functionalities.